Dental and Oral Health Empowerment Program for Elderly using BULAN KESGILUT Book - Wibowo, Alvita; Arsyilviasari, Rima; Meilena, Tiara; Setyowati, Ayu; Gabriella, Retta; Latifah, Nur; Setijanto, R. Darmawan (Faculty of Dental Medicine Universitas Airlangga, 2020)
Background: Dental and oral health problems occur in all age groups, including the elderly. Dental caries is one of the dental and oral health problems. An epidemiological study reported that 83.5% out of 91 elderly respondents did not have a routine dental check-up. The data concluded that those who routinely have dental check-up had a lower caries risk than the others. The public health centre did not have data about the total of elderly visitors in the dental poly unit. The BULAN KESGILUT book aimed to help to monitor dental and oral health status in the elderly. Purpose: To help the dental poly and elderly visitors to have medical records related to dental and oral health using BULAN KESGILUT book. Methods: The program adopted an indirect health education method involving cadres and dentists from the public health centre. The counselling was done by group. The lecture consisted of dental and oral health material printed in the BULAN KESGILUT book. We have then informed the dentists on how to record the dental and oral health status in the BULAN KESGILUT book and educate the cadres on how to read those records. Results: The mean of cadres' understanding of BULAN KESGILUT book was 97.92%, and the mean of cadres' information dissemination related to BULAN KESGILUT book was 55.81%. Conclusion: The program results showed that BULAN KESGILUT was an effective media in monitoring dental and oral health status in the elderly. However, a continuous promotion by the cadres and the public health center is necessary